Augmenting Traditional Networks With Data Buys Can Support Science, as Well as Operations - J. L. Gannon; N. Lugaz (Space Weather)
Key Points A data buy is where an entity purchases access to a set of data or a data stream, instead of operating the sensors themselves Efficiency and cost are factors that drive this kind of data access over the more traditional methods of running a network As data buys evolve, new solutions will need to be developed for public access to data archives that do not compromise operational integrity